2014
DOI: 10.1002/cbin.10327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbon‐ion beam irradiation on the angiogenic response in lung adenocarcinoma A549 cells

Abstract: Radiotherapy has been focused mainly on killing cancer cells, and little attention has been paid to the process supporting tumor growth and metastasis, including the process of angiogenesis. To investigate the effects of carbon-ion irradiation on angiogenesis in lung cancer cells, we examined the expression of vascular endothelial growth factor and basic fibroblast growth factor in the tumor conditioned medium (TCM) of A549 cells exposed to carbon-ion or X-ray irradiation, as well as endothelial cell growth, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In the present study, there was no notable difference in the expression of VEGF in Tca8113 cells irradiated with X-rays compared with non-irradiated cells. By contrast, VEGF levels significantly decreased in cells irradiated with carbon ions compared with non-irradiated cells supporting the results of a previous study by Liu et al (37), who reported that carbon ion radiation decreased VEGF secretion in lung adenocarcinoma A549 cells. As the immunofluorescence assay can only show the location of the target protein and cannot detect the molecular weight of the protein, the effect of irradiation on VEGF expression needs to be confirmed using western blot analysis in future experiments.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, there was no notable difference in the expression of VEGF in Tca8113 cells irradiated with X-rays compared with non-irradiated cells. By contrast, VEGF levels significantly decreased in cells irradiated with carbon ions compared with non-irradiated cells supporting the results of a previous study by Liu et al (37), who reported that carbon ion radiation decreased VEGF secretion in lung adenocarcinoma A549 cells. As the immunofluorescence assay can only show the location of the target protein and cannot detect the molecular weight of the protein, the effect of irradiation on VEGF expression needs to be confirmed using western blot analysis in future experiments.…”
Section: Discussionsupporting
confidence: 90%
“…Conventional radiotherapy using gamma rays or X-rays is facing various difficulties like it lacks dose-localization to the target tumor cells, it grows radio-resistance, it is not effective for hypoxic tumors or deep seated tumors and importantly it triggers cancer metastasis by activating matrix metalloproteinases in various cancer cell-types as discussed in the Background section. On the contrary, high LET radiation or charged particles like carbon ion has better potential to suppress metastatic nature of cancer cells in vitro and in vivo [ 56 , 57 ] including its other beneficial roles over low LET radiations as described earlier. But the detailed mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Some pro-inflammatory and pro-angiogenic genes, such as CCL2 , CSF1 , IL8 and PDGFB , seemed to be overexpressed by the co-culture configuration no matter if the cells were irradiated or not. It is however interesting to note that two studies reported angiogenic suppressive effects after irradiation of cancer cells with protons [ 34 ] or carbon ions [ 35 ]. In EC, CCL5 , IL8 and CXCL10 genes were overexpressed independently of irradiation and PDGFB and CSF1 gene overexpression had also similar profile to the one of FAS .…”
Section: Discussionmentioning
confidence: 99%